Perlindungan Hukum Atas Kehilangan Saldo Pengguna E-Wallet Dana di Tinjau Dari Fatwa DSN MUI No.16/Dsn Mui/Ix/2017 Tentang Uang Elektronik Syariah (Studi Kasus Pengguna E-Wallet Dana di Kecamatan Medan Tembung, Kota Medan) - Kamila, Zahra; Efendi, Rahmad (UNES Law Review, 2023)
This research discusses consumer protection against loss of balance for DANA E-Wallet users from the perspective of DSN MUI Fatwa No. 16/DSN-MUI/IX/2017 concerning Sharia Electronic Money. Considering the growth in e-wallet use in Indonesia, especially in Medan Tembung District, Medan City, losing customer balances requires strong protection. The DSN MUI fatwa on sharia electronic money provides guidance regarding the application of sharia principles in the use of electronic money and its implementation. This research uses empirical methodology and focuses on real cases in Medan Tembung District. The research results show that there are several weaknesses in the current legal protection of DANA E-wallet users, especially related to the claim and rescue settlement mechanism. It is hoped that the recommendations from this research can be a consideration for regulators and e-wallet service providers to increase consumer protection, in accordance with sharia principles and existing fatwas.